Fertilisation and nutrition of the oocyte in the calcified sponge Petrobiona massiliana. In: Rützler K (ed) New Perspectives in Sponge Biology. Smithsonian Institution Press, Washington DC. - Gallissian, M.-F.; Vacelet, J. (1990)
Transmission electron microscope observations of some stages of the oocyte development of Petrobiona massiliana have revealed some added information...
Proceedings of the 3rd International Sponge Conference